Validation of a simple inductively coupled plasma mass spectrometry method for detecting urine and serum iodine and evaluation of iodine status of pregnant women in Beijing. (18th August 2018) - Yu, Songlin; Yin, Yicong; Cheng, Qian; Han, Jianhua; Cheng, Xinqi; Guo, Ye; Sun, Dandan; Xie, Shaowei; Qiu, Ling
Abstract: Rapid and simple method for serum and urine iodine is necessary for iodine-related diseases. This study aimed to establish and validate a simple and rapid method for quantification of iodine in human urine and serum using inductively coupled plasma mass spectrometry (ICP-MS). Generally, samples were diluted using water with 1.5% isopropanol and 7 mmol hydrous ammonium before analysis by the ICP-MS. Performance of the method was validated, and the urine and serum iodine levels of 72 pregnant women were analyzed. Results showed that the lower limit of detection of the ICP-MS method was 0.87 µg/L. No significant memory effects were observed. Recovery in both serum and urine was approximately 100%. Compared with NIST SRM3668, bias was <1%, exhibiting good accuracy. The inter-run coefficients of variation (CVs) for serum and urine iodine were 2.8–3.5% and 3.5–6.7%, respectively, and total CVs for serum and urine iodine were 3.2–3.7% and 3.9–6.7%, respectively. Comparison of the iodine results obtained by the ICP-MS method and the conventional S–K method revealed excellent correlation ( r = 0.984, mean bias = –1.7%). The median urine iodine of pregnant women (125.5 μg/L) was lower than that of WHO criteria for iodine deficiency (median urinary iodine <150 μg/L) while 55.6% of the individuals with urine iodine level less than 150 μg/L. The median serum iodine level of the pregnant women was 69.0 μg/L. In conclusion, a rapid and simple ICP-MS method for urine and serum iodine measurements has been established and validated, and the pregnant women in Beijing may still suffer from insufficient iodine intake. Abbreviations: CV coefficients of variation HPLC high-performance liquid chromatography ICP-MS inductively coupled plasma mass spectrometry KED kinetic energy discrimination KI potassium iodide LOD limit of detection S–K Sandell–Kolthoff reaction PUMCH Peking Union Medical College Hospital